Characteristics of an effective secondary school design thinking curriculum - Aflatoony, Leila; Wakkary, Ron; Hawryshkewich, Andrew (FormAkademisk, 2018)
This study examines the effectiveness of course materials, design methods and teaching strategies in a design thinking-based curriculum. As part of a multiple case study, we developed, ran and studied an interaction design course for Canadian students in grade 9 and grade 10 (14–15 years old). We gathered qualitative data in the forms of interviews of students and teachers at the end of each class and at the end of the course, and we observed their activities and performance throughout the course. We also evaluated the curriculum by tracking the changes we made and justifying the intentions behind these curriculum modifications in the context of the research. From this research, three main curriculum characteristics were found to be essential for a design thinking course to be effective and engaging: experiential activities, real-world applications and characterised consequences. We recommend that design educators consider these characteristics.